The encyclopedia of historic and endangered livestock and poultry breeds - Dohner, Janet Vorwald, 1951- (Yale agrarian studies., 2001)
"The need to preserve farm animal diversity is increasingly urgent, says the author of this definitive book on endangered breeds of livestock and poultry. Farmyard animals may hold critical keys for our survival, Jan Dohner warns, and with each extinction, genetic traits of potentially vital importance to our agricultural future or to medical progress are forever lost."--Jacket